Meningkatkan Teknik Dasar Servis Bawah Pada Permainan Bola Voli Melalui Metode Latihan - Pou, Elsa Tiara; Nuhiya, Akmal; Tololiu, Bayu Saputra; Maspeke, Wahyu Syahbani; Nabu, Adrian; Hidayat, Joni Taufik; Ikhsan, Haerul; Ilham, Al (Universitas Negeri Gorontalo, 2025)
This research aims to improve the underhand serve technique in volleyball through training methods in Grade V students at SD State 1 Bonepantai Elementary School. Based on the data obtained from classroom action research, with the application of the training method as a learning method in the volleyball game phase in physical education subjects conducted in cycle I, it was found that students' confidence increased significantly. It was described in the initial observation phase, the mastery level of the basic underhand serve technique in volleyball game in Grade V students at SD State 1 Bonepantai Elementary School increased from 48.5% at the initial observation to 70.88% at the end of cycle I, continued to cycle II and increased to 80.61% at the end of cycle II. Thus, this proves that using the training method in learning influences improving the learning outcomes of the basic underhand serve technique in volleyball.